Beyond 1 Tb/s Intra-Data Center Interconnect Technology: IM-DD OR Coherent? - Zhou, Xiang; Urata, Ryohei; Liu, Hong (Journal of lightwave technology, 2020)
We discuss technology options and challenges for scaling intra-datacenter interconnects beyond 1 Tb/s bandwidths, with focus on two possible approaches: pulse amplitude modulation (PAM)-based intensity modulation-direct detection (IM-DD) and baud-rate sampled coherent technology. In our studies, we compare the performance of various orders of PAM modulation (PAM4 to 8). In addition to these fixed PAM signaling options, a flexible PAM (FlexPAM) technique leveraging granularity in spectral efficiency (SE) is proposed to maximize link margin. For baud-rate sampled coherent technology, we propose a simplified digital signal processing (DSP) architecture to bring down power consumption of the coherent approach closer to that of IM-DD PAM. We also propose two new phase noise tolerant 2D coherent modulation formats to relax the laser linewidth requirement. In closing, a comparative study of fixed IM-DD PAM versus coherent polarization multiplexed-quadrature amplitude modulation (PM-QAM) is presented for a 1.6 Tb/s solution (200 Gb/s per dimension), with consideration of link loss/reach budget, power consumption, implementation complexity, as well as fan-out granularity.